Ipomoea laxiflora H. J. Chowdhery & Debta (Convolvulaceae): A New Distribution Record for North Maharashtra - Kapadane, K K; Shelke, R A; Rajput, K S; Raole, V M (Plantae Scientia, 2022)
Ipomoea laxiflora H. J. Chowdhery & Debta (Convolvulaceae) is reported as an addition to the flora of Dhule, Jalgaon and Nandurbar Districts and as a new distributional record for North Maharashtra. Morphologically, present species similar to I. triloba L., and is separated by absence of hairs on ovary and capsules. So far, the present species is reported from northern part of India, Gadchiroli (Vidarbha) and Ichalkaranji (Kolhapur District). A brief description, distribution, conservation status is given to facilitate easy identification of I. laxiflora in the field.